Priročnik primerov pedagoške prakse poučevanja in učenja na univerzitetnem nivoju z osredotočenostjo na naravoslovno-matematična področja - Bokal, Drago; Klemenčič, Eva; Repnik, Robert (University of Maribor Press, 2022)
Handbook of Pedagogical Practices’ Examples of Teaching and Learning at the University Level with a Focus on Natural Sciences and Mathematics. The Handbook of pedagogical practices’ examples of teaching and learning at the university level with a focus on natural sciences and mathematics is intended for all university teachers, who want to introduce proven pedagogical practices into their teaching in order to improve academic success and empower students. The handbook presents the process of acquiring knowledge from discovery to application through a scale of technology readiness levels. We want to emphasize the limited resources such as knowledge, intelligence, emotional intelligence, empathy, time, attention, trust, and the importance of their optimal use. Through concrete examples of highly effective pedagogical practices, we want to encourage teachers to introduce innovative methods into the pedagogical process and combine them with traditional ones.